Respon Mahasiswa Terhadap Perkuliahan Berbasis Kearifan lokal Pada Mata Kuliah Kajian Fisika Sekolah Menengah - Hikmawati Hikmawati; I Wayan Suastra (Kappa Journal, 2021)
This study aims to describe student responses to local wisdom-based lectures in the High School Physics Studies course. This type of research is descriptive research. The research subjects were 27 5th semester students at one of the universities in the city of Mataram. The research was carried out from 18 August 2021 to 27 October 2021 with a total of 10 meetings. Lectures are conducted online through the Learning Management System (LMS). The research data was obtained by providing response questionnaires to students in the form of a google form at the end of the lecture. Student responses are said to be positive towards local wisdom-based lectures in terms of 4 aspects, namely happy, new, enthusiastic, and interested, which is at least 75%. Each aspect has 5 components that are assessed, namely lecture material, LMS discussion forums, student learning methods, lecturers' teaching methods, and assessment in the form of assignments. The results showed that 96% of students said they were happy, 78% of students said they were new, 89% of students said they were enthusiastic, and 91% of students said they were interested in lectures based on local wisdom. Thus, students expressed a positive response to local wisdom-based lectures on each component of the assessment.